Participatory Integrated Climate Services for Agriculture (PICSA) Intermediary Training, Zomba District, Malawi - Gathenya, John (2017)
A Participatory Integrated Climate Services for Agriculture (PICSA) intermediary training workshop was held in Zomba District, Malawi in July 2016. The workshop aimed to train intermediaries to understand the PICSA approach so they can train other intermediaries. The intermediaries are expected to integrate the PICSA approach in their normal work routines so that PICSA can be scaled out, with minimal resources. Once trained, farmers would be able to use participatory planning tools to make informed decisions based on accurate, location-specific, climate and weather information and locally relevant crop, livestock and livelihood options.